Culture and household saving - Benjamin Guin (European Central Bank (ECB), 2017)
This paper examines the role of culture in households' saving decisions. Exploiting the historical language borders within Switzerland, I isolate the effect of households' exposure to certain language groups from economic, institutional, demographic and geographic factors for a homogeneous and representative sample of households. The analysis uses the Swiss Household Panel which I complement with geographic and socio-economic data. I show that low- and middle-income households located in the German-speaking part are more than 11 percentage points more likely to save than similar households in the French-speaking part. In line with the existing literature, I show that these differences across language regions are consistent with different distributions of time preferences. By contrast, I do not find clear evidence for risk sharing during times of financial distress.
Keywords: Z1; D12; E21; D91; 330; Household Finance; Saving; Culture; Language; Household Economics